What Do Physiotherapists Know About Techno-Therapy? - Esra Dogru HUZMELI; Ozden GOKCEK; Sabiha BEZGIN; Yagmur CAM; Hasan HALLACELI; Senem URFALI; Murat GUNTEL; IremKARANKI (Editura Universităţii din Oradea, 2020)
Aim: The aim of this study was to examine the knowledge of the physiotherapists about techno-therapy, so we want to take attention on the importance of updating the physiotherapist themselves about new rehabilitation devices that the physiotherapists use and to encourage the in-service training regularly. Methods: The study group consists of 24 physiotherapists working in Hatay. The survey consisted mostly of open-ended questions. These are the questions that were asked to the physiotherapists: Q1: Do you know what is the virtual reality?, Q2: What does augmented therapy mean?, Q3: What do you know about technological equipment to help patients that have communication problems?, Q4: What do you know about wearable rehabilitation technology ?, Q5: What do you know about robotic rehabilitation ?, Q6: Do you use any technologic equipment in your treatment ?, Q7: Did you have courses about technology during your university education ?. The first 5 questions' answers were assessed as "false", "true" or "do not know" and the last two questions as "yes" or "no" by an assistant professor. Results: Fourteen females, ten males aged between 22-60 years (X+SD=29.83±8.8) totally 24 individuals were included in the study. Questions (Q) results are following:Q1:23 of their answers were true, 1 was false;Q2:All of them answered as do not know; Q3:1 of them answered as false, 1 of them as true and 22 of them as do not know; Q4: 1 of them answered as false, 1 of them as true and 22 of them as do not know; Q5: 18 of them answered as true, 6 of them as false; Q6: 6 of them answered as yes, 18 of them as no; Q7:5 of them answered as yes, 19 of them as no. Discussion: As a result, we learned that most of the physiotherapists do not have sufficient knowledge about techno-therapy devices and that they have heard some applications for the first time during the survey. We concluded that physiotherapists need to follow up on current practice and devices and that universities can assume the role of mentors and organize instruction at regular intervals to help physiotherapists to update their knowledge about new technologies.